The Effect Of Compensation and Job Satisfaction On Employee Work Productivity (At PT. Rumah Sakit Prasetya Bunda Tasikmalaya) - Akhsay, Mochamad; Barlian, Barin; Risana, Dudu (Universitas Dehasen Bengkulu, 2024)
The purpose of this study was to determine compensation, job satisfaction, and work productivity of employees at Rumah Sakit Prasetya Bunda Tasikmalaya. The effect of compensation on the work productivity of Rumah Sakit Prasetya Bunda Tasikmalaya employees. The effect of job satisfaction on the work productivity of Rumah Sakit Prasetya Bunda Tasikmalaya employees. This research includes quantitative research in the sense that in this study it uses numbers, starting from data collection to interpreting data with statistical tests. The data collection technique used was a survey method. The data analysis technique used was descriptive statistical analysis and multiple linear regression tests. The results of the study show that compensation is included in the very good category, job satisfaction is included in the good category, and work productivity for Rumah Sakit Prasetya Bunda Tasikmalaya employees is included in the good category. There is a positive effect of compensation on work productivity for Rumah Sakit Prasetya Bunda Tasikmalaya employees. There is a positive influence of job satisfaction on work productivity for Rumah Sakit Prasetya Bunda Tasikmalaya employees.